West of the border : the multicultural literature of the Western American frontiers - Lape, Noreen Groover, 1966- (Ohio University Press, 2000)
"James P. Beckwourth, a half-black fur trader; Sarah Winnemucca Hopkins, a Paiute translator; Salishan author Mourning Dove; Cherokee novelist John Rollin Ridge; Sui Sin Far, an Anglo-Chinese short story writer, and her sister, romance novelist Onoto Watanna; and Mary Austin, a white southwestern writer - each of these intercultural writers faces a rite of passage into a new social order. Their writings negotiate their various frontier ordeals: the encroachment of pioneers on the land; reservation life; assimilation; Christianity; battles over territories and resources; exclusion; miscegenation laws; and the devastation of the environment." "In West of the Border Noreen Groover Lape raises issues inherent in American pluralism today by broaching timely concerns about American frontier politics, conceptualizing frontiers as intercultural contact zones, and expanding the boundaries of frontier literary studies by giving voice to minority writers."--Jacket.